2015
DOI: 10.1038/srep18110
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenic transport and K+ ion channel expression by the human endolymphatic sac epithelium

Abstract: The endolymphatic sac (ES) is a cystic organ that is a part of the inner ear and is connected to the cochlea and vestibule. The ES is thought to be involved in inner ear ion homeostasis and fluid volume regulation for the maintenance of hearing and balance function. Many ion channels, transporters, and exchangers have been identified in the ES luminal epithelium, mainly in animal studies, but there has been no functional study investigating ion transport using human ES tissue. We designed the first functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 21 publications
3
25
0
1
Order By: Relevance
“…13,15,16,40 Through small angle electron diffration study, 13 CDW wave vector has been confirmed to be (n/3, 0, 0), where n (= 1, 2) is the order of reflection, which requires tripling of unit cell be-low T CDW . Furthermore, theoretical prediction of coexistence of CDW and superconductivity in LaPt 2 Si 2 by Kim et al 41 has been confirmed experimentally in our earlier reports. 15,16 On the other hand, electronic structure calculation predicts quasi-two-dimensional nature of the Fermi surface 42 similar to that seen for iron pnictides.…”
supporting
confidence: 80%
“…13,15,16,40 Through small angle electron diffration study, 13 CDW wave vector has been confirmed to be (n/3, 0, 0), where n (= 1, 2) is the order of reflection, which requires tripling of unit cell be-low T CDW . Furthermore, theoretical prediction of coexistence of CDW and superconductivity in LaPt 2 Si 2 by Kim et al 41 has been confirmed experimentally in our earlier reports. 15,16 On the other hand, electronic structure calculation predicts quasi-two-dimensional nature of the Fermi surface 42 similar to that seen for iron pnictides.…”
supporting
confidence: 80%
“…Thirdly, the high graphitization degree (Figure b) and the formation of carbon nanosheets (Figure c and d, Figure S4) of S3/N‐CNS800 are very important to improve the ORR catalytic activity. Finally, the high specific surface area and porous structure can be beneficial for the exposure of those active sites and splendid mass transport efficiency of the electrolyte (contain O 2 , H + , OH − , H 2 O) . Therefore, both of N‐CNS800 and S3/N‐CN800 show the poor ORR activity (Figure b), which can be partially due to the absence of thiophenic‐S active sites (Table S1) and the small specific surface area (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25][26] Further, changing the symmetry of a material via optically induced phase transitions offers new ways to manipulate material properties on ultrafast timescales. [27,28] Research about the ultrafast response of two dimensional materials like TMDC in connection with their rich electronic phase diagrams, e.g., superconductivity [29,30] or CDW phases, may well be important for understanding the basic physics for the design of future ultrafast (optoelectronic or optospintronic) devices. [31][32][33] Materials like 1T-TaS 2 , 2H-TaSe 2 , and 1T-TiSe 2 have been studied in some detail, [34][35][36] but there still is a controversy about the origin of the CDW phases in those materials, especially for 1T-TiSe 2 .…”
Section: Introductionmentioning
confidence: 99%